The Combined Effects of SST and the North Atlantic Subtropical High-Pressure System on the Atlantic Basin Tropical Cyclone Interannual Variability - Albenis Pérez-Alarcón; José C. Fernández-Alvarez; Rogert Sorí; Raquel Nieto; Luis Gimeno (Atmosphere, 2021)
The combined effect of the sea surface temperature (SST) and the North Atlantic subtropical high-pressure system (NASH) in the interannual variability of the genesis of tropical cyclones (TCs) and landfalling in the period 1980–2019 is explored in this study. The SST was extracted from the Centennial Time Scale dataset from the National Oceanic and Atmospheric Administration (NOAA), and TC records were obtained from the Atlantic Hurricane Database of the NOAA/National Hurricane Center. The genesis and landfalling regions were objectively clustered for this analysis. Seven regions of TC genesis and five for landfalling were identified. Intercluster differences were observed in the monthly frequency distribution and annual variability, both for genesis and landfalling. From the generalized least square multiple regression model, SST and NASH (intensity and position) covariates can explain 22.7% of the variance of the frequency of TC genesis, but it is only statistically significant (p < 0.1) for the NASH center latitude. The SST mostly modulates the frequency of TCs formed near the West African coast, and the NASH latitudinal variation affects those originated in the Lesser Antilles arc. For landfalling, both covariates explain 38.7% of the variance; however, significant differences are observed in the comparison between each region. With a statistical significance higher than 90%, SST and NASH explain 33.4% of the landfalling variability in the archipelago of the Bahamas and central–eastern region of Cuba. Besides, landfalls in the Gulf of Mexico and Central America seem to be modulated by SST. It was also found there was no statistically significant relationship between the frequency of genesis and landfalling with the NASH intensity. However, the NASH structure modulates the probability density of the TCs trajectory that make landfall once or several times in their lifetime. Thus, the NASH variability throughout a hurricane season affects the TCs trajectory in the North Atlantic basin. Moreover, we found that the landfalling frequency of TCs formed near the West Africa coast and the central North Atlantic is relatively low. Furthermore, the SST and NASH longitude center explains 31.6% (p < 0.05) of the variance of the landfalling intensity in the archipelago of the Bahamas, while the SST explains 26.4% (p < 0.05) in Central America. Furthermore, the 5-year moving average filter revealed decadal and multidecadal variability in both genesis and landfalling by region. Our findings confirm the complexity of the atmospheric processes involved in the TC genesis and landfalling.